PENGARUH PERAN ORANG TUA TERHADAP HASIL BELAJAR SISWA - Henceyana Saragih; Regina Sipayung; Dyan Wulan Sari HS; Darinda Sofia Tanjung (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study aims to determine the effect of the role of parents on student learning outcomes on the theme of the area where I live in class IV SD Negeri 094097 Simpang Pongkalan Tongah. The research was conducted on May 9, 2021. The research method used was a quantitative survey type. The sample in this study were fourth grade students with a total of 31 students. The data collection tool used is a questionnaire or questionnaire. This study uses the normality test with the results of 0.200 ≥ 0.05 where the data is normally distributed. From the correlation test, it is known that the calculation results obtained rcount 0.606, which means there is a positive influence. The significance test was carried out to test the hypothesis, namely by comparing the value of tcount with ttable. Obtained the value of tcount = 4.103 while ttable = 1.699. Because tcount ttable (4.103 ≥ 1.699) then Ha is accepted and H0 is rejected. Through the t test, it can be concluded that there is a significant influence between the role of parents and student learning outcomes.